2014
DOI: 10.1021/nl503834b
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Strain Induced Magnetic Phase Segregation in Manganite Thin Films

Abstract: Epitaxial strain alters the physical properties of thin films grown on single crystal substrates. Thin film oxides are particularly apt for strain engineering new functionalities in ferroic materials. In the case of La(2/3)Ca(1/3)MnO(3) (LCMO) thin films, here we show the first experimental images obtained by electron holography demonstrating that epitaxial strain induces the segregation of a flat and uniform nonferromagnetic layer with antiferromagnetic (AFM) character at the top surface of a ferromagnetic (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…By doping SrMnO 3 with La, the system becomes FM in the range of 20 -40 % La content in bulk, but magnetic properties of manganites not only depend on La doping but on strain as well. 28,29 Coupling the FM and AFM order of both materials by means of exchange bias effect would open the door to the control of the magnetic properties applying an electric field in multiferroic heterostructures. 30 We report the dependence of this phenomenon on the epitaxial strain and temperature in SMO / LSMO bilayers.…”
mentioning
confidence: 99%
“…By doping SrMnO 3 with La, the system becomes FM in the range of 20 -40 % La content in bulk, but magnetic properties of manganites not only depend on La doping but on strain as well. 28,29 Coupling the FM and AFM order of both materials by means of exchange bias effect would open the door to the control of the magnetic properties applying an electric field in multiferroic heterostructures. 30 We report the dependence of this phenomenon on the epitaxial strain and temperature in SMO / LSMO bilayers.…”
mentioning
confidence: 99%
“…5 The growth of epitaxially strained or relaxed thin films with reasonable lattice matching can be accomplished via different routes, but in every case, it requires certain growth parameters and the procedure to be followed. However, one of the key aspects of such approaches is the formation of the strained/relaxed film directly during growth, which typically requires high temperatures and high or ultra-high vacuum.…”
mentioning
confidence: 99%
“…The films were grown on 5 × 5 × 0.5 mm 3 (001)-oriented STO, LSAT, and LAO single-layer substrates. The deposition of single LSMO films was performed at a substrate temperature of 830 °C and oxygen pressure of 400 mTorr, as described elsewhere [12], [44], followed by a cooling cycle between 830 and 20 °C at an oxygen pressure of 700 Torr to favor optimal oxygen stoichiometry, at a cooling rate of 10 °C/min. In the case of the bilayers, the BTO film was then deposited at 830 °C and an oxygen pressure of 3 mTorr.…”
Section: Methodsmentioning
confidence: 99%
“…For the LSMO and other manganites, the effect of the substrate-induced strain on its magnetic properties in single-layer configuration has been widely studied, particularly the influence of strain on the magnetic anisotropy [15], [16]. Depending on the type and magnitude of the imposed biaxial strain (compressive or tensile) [17], the pure cubic-symmetry (or biaxial) magnetic anisotropy of the unstrained LSMO film can be altered in different ways: (i) giving rise to the appearance of a uniaxial in-plane magnetic anisotropy contribution, which is significantly stronger than the cubic one [15], [18]- [21], (ii) inducing an out-of-plane magnetic anisotropy in compressivestrained films [22]- [26], and (iii) suppressing the FM ordering in a small region of the layer, close to the substrate interface, due to large crystal deformations, resulting in 4 the formation of a dead layer with antiferromagnetic-insulating behavior [12], [27]- [31]. Moreover, it was found that a uniaxial magnetic anisotropy is artificially induced in LSMO films grown on ferroelectric BFO substrate when the polarization of the FE domains is switched into highly aligned stripe domains, inducing a magnetic easy axis in the FM layer parallel to the polarization direction [32], [33].…”
Section: Introductionmentioning
confidence: 99%